2008
DOI: 10.1123/jab.24.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Strain in the Tibial and Plantar Nerves with Foot and Ankle Movements and the Influence of Adjacent Joint Positions

Abstract: We studied the influence of different positions in neighboring joints on strain in the tibial and plantar nerves during ankle and toe movements. Tibial nerve strain at the ankle was measured during ankle dorsiflexion in ten cadavers; plantar nerve strain was measured during toe extension. Tibial nerve strain increased with ankle dorsiflexion (mean increase: 3.9%) and strain was higher when the nervous system was pretensioned by either knee extension or hip flexion (p ≤ .011). Strain was even higher when the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Finally, limb position is an important consideration in the clinical use of neurodynamic mobilization as there is a mutual relationship between joint position and the amount of strain and excursion. 29,34,60,61 Therefore, additional studies investigating various limb positions on fluid dispersion are warranted. Limitations of this current study include the inability to generalize the findings to live subjects due to active physiological processes, the inability to completely generalize the results to other peripheral nerves or nerve roots, and the inability to generalize the findings to nerves exhibiting a loss of elasticity due to fibrosis or adhesions, 46,63 which may alter the manner in which fluid is dispersed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, limb position is an important consideration in the clinical use of neurodynamic mobilization as there is a mutual relationship between joint position and the amount of strain and excursion. 29,34,60,61 Therefore, additional studies investigating various limb positions on fluid dispersion are warranted. Limitations of this current study include the inability to generalize the findings to live subjects due to active physiological processes, the inability to completely generalize the results to other peripheral nerves or nerve roots, and the inability to generalize the findings to nerves exhibiting a loss of elasticity due to fibrosis or adhesions, 46,63 which may alter the manner in which fluid is dispersed.…”
Section: Discussionmentioning
confidence: 99%
“…29,30,34,[60][61][62] While these studies provide valuable information regarding peripheral nerve movement and strain, they provide no insight into the mechanisms responsible for the benefits of using neurodynamic mobilization. Furthermore, no studies were found that address the effects of neurodynamic mobilization on nerves exhibiting pathophysiological responses such as impaired nerve conduction, ischemia, inhibited axonal transport, or intraneural edema.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with other studies, the calcaneal tendon was cut to obtain adequate ankle dorsiflexion. 1,2,8 The exact effect of transecting the calcaneal tendon on tibial nerve biomechanics is unknown but would most likely have had a comparable effect for the different sequences. The DVRT strain gauge was inserted into the nerve with 2 barbed pins separated by approximately 3 cm.…”
Section: Strain Measurementsmentioning
confidence: 99%